2005
DOI: 10.1111/j.1473-2165.2005.00306.x
|View full text |Cite
|
Sign up to set email alerts
|

Striae distensae in darker skin types: the influence of melanocyte mechanobiology

Abstract: As striae distensae are in part under the influence of skin stretching, their colors are likely to be controlled by some mechanobiological process activating or inhibiting melanogenesis in people of darker complexion. No argument involving an inflammatory mechanism is supported by the present observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 25 publications
3
38
0
2
Order By: Relevance
“…Rarely, in people with darker skin, striae appear darker because of increased melanization as striae cerulae (blue) or striae nigrae (black) 14. The color of SD is linked to the stage of their evolution and to the influence of melanocyte mechanobiology 5. Also, in case of striae nigrae and striae cerulae, the releasing of cytokines, such as the stem cell factor and hepatocyte growth factor, may induce epidermal hyperpigmentation 2…”
Section: Introductionmentioning
confidence: 99%
“…Rarely, in people with darker skin, striae appear darker because of increased melanization as striae cerulae (blue) or striae nigrae (black) 14. The color of SD is linked to the stage of their evolution and to the influence of melanocyte mechanobiology 5. Also, in case of striae nigrae and striae cerulae, the releasing of cytokines, such as the stem cell factor and hepatocyte growth factor, may induce epidermal hyperpigmentation 2…”
Section: Introductionmentioning
confidence: 99%
“…The livid facial appearance, especially marked on the cheeks, is due to the skin thinning at a site where the subpapillary venous plexus is nearer the surface than in most other body sites. Striae distensae are the results of loosening structure of the dermis at sites of maximal stress and appear to represent elastic fibre failure owing to the stress [44,45]. These lesions are normally evident to some degree in adolescence and pregnant women, but are more prominent in Cushing syndrome.…”
Section: Endocrinopathies and The Skinmentioning
confidence: 99%
“…9 Cushing syndrome or long term administration of topical/oral corticosteroids may cause the developing of striae. 5,[10][11][12][13] Genetic susceptibility can definitely have a major role as well; however, the precise mechanism has not completely elucidated. Tung et al performed some accurate genome analysis and demonstrated the collapse of elastic microfibrils as the etiology of some cases of striae distensae.…”
Section: Introductionmentioning
confidence: 99%